CLINICAL SYMPTOMS, EFFECTIVE CURE AND HAZARDOUS EFFECTS OF FABRY DISEASE ON HUMAN HEALTH - Ali, Sikander; Naeem, Sania; Faisal, Fatima (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Fabry disease is a lysosomal storage disorder which is caused by the deposition of globotriaosylceramide (GL-3) due to the deficiency of a-galactosidase A leading to the change in metabolism. This is a pan ethnic disorder and more frequently present in males than in females. Children may also have the symptoms of this disease. The major symptoms of fabry’s disease are pain in body, anaemia, fever, kidney problems, dermatological symptoms and cardiovascular disease and strokes. The disease can be analysed by the DNA testing in amniotic cells and chorionic villi and enzyme activity. Atypical variants or available genetic therapy may complicate the genetic counselling. The disease specific treatment has been introduced in which recombinant human galactosidase enzyme is used to investigate the fabry’s disease, this treatment is known as enzyme replacement therapy. Renal transplantation and dialysis have also been introduced. Analgesic drugs, antiarrhythmic agents and nephroprotections are used to relieve pain.